Antenna-in-Package Using IC-Embedded Metal Fan-Out Wafer-Level Package for D-Band Applications - Ju-Yong Lee; Jein Yu; Wansik Kim; Jong-Min Yook (IEEE Access, 2025)
In this study, we present a low interconnection loss antenna-in-package (AiP) using a chip-embedded metal fan-out wafer-level package (mFOWLP) technology for D-band (110–170 GHz) applications. The package configuration enables interconnection with radio frequency monolithic microwave integrated circuits (RF MMIC) through redistribution layers (RDL) and microvias, effectively reducing the signal path loss. Moreover, the narrow bandwidth of the series-fed patch antenna can be effectively overcome by employing a low-loss polyimide (PI) multilayer structure. The fabricated AiP comprised a $1× 8$ stacked Chebyshev distribution series-fed patch antenna with a dummy chip. The proposed AiP achieved an interconnection loss of 0.19 dB, and an impedance bandwidth of 18.25 GHz. The peak antenna gain was measured to be 14.2 dBi.